Quantification of the influence of endotoxins on the mechanics of adult and neonatal red blood cells - Itō, Hiroaki; Kuß, Navina; Tanaka, Motomu; Pöschl, Johannes (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2015)
In this study, we physically modeled the influence of endotoxin-induced sepsis symptoms on human red blood cells (RBCs) by quantifying the impact of endotoxins on the cell mechanics by the analysis of Fourier-transformed mean square amplitude of shape fluctuation, called flicker spectroscopy. With the aid of a microfluidic diffusion chamber, we noninvasively determined principal mechanical parameters of human RBCs in the absence and presence of endotoxins for individual RBCs for the first time. Because of the elongation of saccharide chain length of endotoxins, we found an increase in the morphological transition from discocytes to echinocytes, and monotonic changes in the mechanical parameters. Since septic shocks often cause lethal risks of neonates, we measured the mechanical parameters of neonatal RBCs, and compared them to those of adult RBCs. The quantitative comparison reveals that neonatal RBCs are more susceptible to the effect of endotoxins than adult RBCs. Furthermore, coincubation with the antiseptic peptide P19-2.5 (Aspidasept) with endotoxin results in a slight suppression of the impact of the endotoxin. The strategy proposed in our study can potentially be applied for the quantitative diagnosis of RBCs based on mechanical readouts.
Gesehen am 23.06.2020